2017
DOI: 10.14260/jemds/2017/1031
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Poor Glycaemic Control (Hba1c Levels ≥ 7%) and Higher Incidence of Diabetic Retinopathy in Small Group of Type 2 Diabetes Mellitus Patients Attending Mahatma Gandhi Memorial Government Hospital, Trichy

Abstract: BACKGROUNDDiabetes mellitus is prevalent worldwide. Lot of research work has been done and published on Diabetes Mellitus and its long-term complications. But studies related to the control of diabetes mellitus and its duration with respect to the onset and severity of its microvascular complications are not widely conducted in India. This study was taken up to study the causal relationship between the control (based on HbA1c levels; HbA1c≥7% is considered as poor glycaemic control) and the onset of complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…17 Relationship between diabetic retinopathy and HbA1c levels showed that severity of retinopathy increased as HbA1c levels were raised and this is also supported by many other similar studies. [18][19][20][21] A study conducted by Rebecka Andreasson et al in Sweden showed similar results in children with type 1 diabetes. Increase in HbA1c levels corresponded to the severity of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 89%
“…17 Relationship between diabetic retinopathy and HbA1c levels showed that severity of retinopathy increased as HbA1c levels were raised and this is also supported by many other similar studies. [18][19][20][21] A study conducted by Rebecka Andreasson et al in Sweden showed similar results in children with type 1 diabetes. Increase in HbA1c levels corresponded to the severity of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 89%